Uncertainty and Price Theory - Mills, Edwin S. (Quarterly Journal of Economics, 1959)
I. Introduction, 116. — II. Cost and uncertain demand, 117. — III. Alternative specifications, 118. — IV. Single period horizon: equilibrium conditions, 119. — V. The fundamental theorem, 122. — VI. Example: constant marginal cost, linear riskless demand, and rectangular distribution, 124. — VII. Rising marginal cost, 126. — VIII. Falling marginal cost, 127. — IX. Multi-period horizon, 128.— X. Conclusion, 129.